(untitled) (Agro-Science Letters, 2026)
In scientific discourse, paradigms represent coherent frameworks comprising theoretical assumptions, methodological conventions, and evaluative criteria that collectively define the boundaries and standards of a discipline. Within the field of agricultural extension in India, four distinct paradigmatic orientations have emerged and evolved over time. The earliest of these, rooted in the colonial era and later revived during the 1970s through the Training and Visit (T&V) system across Asia, was Technology Transfer — characterized by a top-down, persuasive, and paternalistic approach to delivering research-based recommendations aimed at boosting farm output through largely conventional models. This was followed by the Advisory Work paradigm, which introduced a more interactive and participatory dimension into extension delivery, emphasizing farmer training, collective organization through self-help groups, and the introduction of farmer field schools and university-based extension frameworks. The most recent evolutionary phase has been marked by a turn toward Facilitation for Empowerment, an approach premised on educational and participatory modes of engagement that foreground horizontal communication, group based problem solving, and farmer-centred methodologies. This review demonstrates that each paradigmatic transition contributed incremental insights to extension practice — beginning with rural development goals and culminating in a dynamic, empowerment-oriented system designed to foster sustainable agricultural transformation.